(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
" In this paper, we use the concept of the soft turing point and join it with separation axioms in soft topological space and investigate the relationship between them and study the most important properties and results of it.